Using Mobile Health Applications to Prevent Preeclampsia in Pregnant Women: A Scoping Review - Hanan Alawiyah Al Joefrie; Iis Rahmawati; Emi Wuri Wuryaningsih (Malahayati Nursing Journal, 2026)
ABSTRACT Preeclampsia remains one of the leading causes of maternal morbidity and mortality worldwide. One of the interventions implemented is health education for pregnant women. However, in practice, this is often hindered by limited time and healthcare personnel. With the advancement of technology, the use of mobile applications in preeclampsia prevention can serve as an alternative educational medium that is easily accessible to pregnant women, as mobile health technology can improve the management of high blood pressure through patient education, facilitate communication between patients and healthcare providers, and support self-monitoring of blood pressure. This study aims to systematically map the use of information systems and digital technology in preventing preeclampsia in pregnant women through a scoping review approach.  The scoping review was conducted following the PRISMA-ScR guidelines. A literature search was performed in international and national scientific databases for articles published from 2018 to 2026 via Google Scholar, Scopus, PubMed, and ScienceDirect. Studies meeting the inclusion criteria were mapped based on research design, type of mHealth intervention, focus, and reported outcomes. Findings from 9 articles indicate that mHealth apps are used for education, early detection, health monitoring, improved access to health services, and increased engagement of pregnant women in health services. The most frequently reported outcomes and objectives of mHealth interventions were early detection and blood pressure monitoring in pregnant women (n=4), while evidence regarding preventive behavioral changes and clinical impacts remains limited. Mobile health applications play a role in supporting preeclampsia prevention, particularly through increased knowledge and engagement among pregnant women. However, further research is needed to evaluate their impact on preventive behavioral changes and clinical outcomes. Keywords: Mobile Health Application, Prevention, Preeclampsia, Pregnant Women.